IDENTITY CRISIS, CONTESTATION, AND CONFLICT WITHIN THE HADRAMI COMMUNITY OF AL-IRSYAD 1990-2007 - Miftahuddin Miftahuddin; Ajat Sudrajat (Journal of Social Studies (JSS), 2017)
At reformation era the identity crisis amongst the members of Al-Irsyad became manifest which directed to split in 20027. This article aims to analyze the Hadrami, the community of Arab descendent, at dealing the issues of Islam and the state at the period of 1990s – 2007. This research find out that at Reformation era, some members of Al-Irsyad suffered from disorientation manifested in the form of internal conflict, contestation, and then split in 2007. It started from the infiltration of the contemporary Salafi which causes its members diverted from the early goals of Al-Irsyad. These disorientated members, based on the Salafi ideology, made movement claimed as a kind of khittah, that is to restore the organization in line with the early goals of Al-Irsyad. This movement, then, created conflict and contestation within Al-Irsyad which 1n 2007 resulted in the split of organization into Al-Irsyad al-Islamiyah and Perhimpunan Al-Irsyad.Key words: Al-Irsyad, Hadrami community, identity crisis, Split, Salafi.